Urbanization in precarious settlements: the case of the Carrapicho Settlement in Várzea Grande – MT - Moraes, Giovanna Erina da Silva; Ravache, Rosana Lia; Godoy, Jeane Aparecida Rombi de; Salmoria, Fabiana Zili (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This study addresses irregular occupations in an environmental preservation area in the Carrapicho Settlement, in Várzea Grande - MT. The research aims to understand the socio-environmental vulnerability of the local population and identify possible means of intervention to improve the quality of life of these communities. As well as discussing the historical relationship between rivers and cities, the importance of conserving wetlands, the lack of coherent public policies to deal with irregular occupation, environmental degradation, and the need for interventions to improve the situation of vulnerable communities in permanent preservation areas. The observational method was used to analyze the current situation in the city of Várzea Grande and the Carrapicho Settlement and its surroundings. In the spatial area, we observed inadequate urban infrastructure, self-built housing with low construction standards, as well as a lot of abandonment and neglect on the part of public authorities.
Keywords: Carrapicho Settlement; Irregular occupation; Socio-environmental Vulnerability